P065: Surveying ED transition of care: satisfaction, awareness of risks and barriers to the implementation of a standardized protocol. (2nd June 2016) - Iseppon, M.; Chauny, J.; Cournoyer, A.; Montplaisir, I.; Daoust, R.; Robert, M.
Abstract : Introduction: Patient handoffs have been identified as the primary cause of error affecting patient safety. The lack of standardization - and the often-avoidable errors that occur as a result - profoundly affect patient care and emergency department (ED) administration. Our study set out to evaluate emergency doctors' awareness of these safety concerns, as well as their satisfaction with handoff practices currently used in their respective EDs. We also aimed to identify the potential barriers to the use of a standardized approach to patient transition of care.Methods: Guided by a modified Delphi method, a 29-question survey was developed by a panel of experts on patient transition of care. A printed version of the survey was distributed to ED doctors attending a local emergency medicine conference. An electronic version was subsequently distributed to all ED doctors registered as members of our provincial professional organizations.Results: We achieved a 68% response rate. Amongst the 309 participants, 51% (95%CI 44-56%) acknowledged that handoffs between emergency doctors are a frequent cause of error related to patient care. Frequent interruptions (77% (95%CI 72-82%)) and heavy workloads (73% (95%CI 68-79%)) were identified as the main factors negatively influencing the quality of handoffs. Despite 61% (95%CI 56-68%) satisfaction with the currently employed methods, 74% (95%CI 68-79%) of the respondents believe that handoffs would benefit from standardization and 83% (95%CI 79-88%) are open to changing their current practices. In addition, 53% (95%CI 48-60%) believe that the tools used for transition of care can be improved. Apprehension regarding the increase of handoff burden (86% (95%CI 81-90%)) was identified as the primary barrier to the implementation of a standardized handoff protocol.Conclusion: Doctors are generally satisfied with current handoff practices used in the ED. Nevertheless, their awareness of the possible risks associated with transition of care may be driving their openness to adapting their practice, potentially towards a more standardized approach given the conceivable benefits to patient safety. In light of these results, we aim to develop a comprehensive, standardized handoff protocol, and to evaluate its applicability in the ED with a prospective study.